2022
DOI: 10.3390/ijms23116111
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin (5-HT) 2A Receptor Involvement in Melanin Synthesis and Transfer via Activating the PKA/CREB Signaling Pathway

Abstract: The 5-HT2A serotonin receptor (HTR2A) has been reported to be involved in the serotonin- or serotonin receptor 2A agonist-induced melanogenesis in human melanoma cells. However, the molecular mechanisms underlying HTR2A in regulating melanogenesis remain poorly understood. In this research, cultured mouse melanoma cell line B16F10, human skin, and zebrafish embryos were used to elucidate the downstream signaling of HTR2A in regulating melanogenesis and to verify the potential application of HTR2A in the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…CREB is a downstream effector of both cAMP and ERK signaling pathways 35,36 and its phosphorylation is related to various physiological processes via serotonin receptors. 37 To further explore the effect of serotonin on 5-HTR1E mediated CREB phosphorylation, we treated 5-HTR1E stable or control HEK293 cells with 1 μM 5-HT in the presence and absence of forskolin. After 20 min.…”
Section: -Htr1e Inhibit Forskolin Stimulated Creb Phosphorylationmentioning
confidence: 99%
“…CREB is a downstream effector of both cAMP and ERK signaling pathways 35,36 and its phosphorylation is related to various physiological processes via serotonin receptors. 37 To further explore the effect of serotonin on 5-HTR1E mediated CREB phosphorylation, we treated 5-HTR1E stable or control HEK293 cells with 1 μM 5-HT in the presence and absence of forskolin. After 20 min.…”
Section: -Htr1e Inhibit Forskolin Stimulated Creb Phosphorylationmentioning
confidence: 99%
“…It was demonstrated that 5-HT is involved in vertebrate melanogenesis and the pathway has been investigated in different model organisms and human cell cultures. For example, 5-HT induced melanin synthesis in different cell lines and zebrafish embryos via 5HT2A receptor by upregulating Tyr and its related enzymes [ 42 , 73 , 74 ]. Fluoxetine, a selective 5-HT reuptake inhibitor, stimulated melanin production in human melanocytes and in zebrafish through 5HT1A/2A and its effect was inhibited by WAY-100635 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serotonergic neurons are mainly distributed in brainstem raphe nuclei, from which projections are sent to wide areas of the brain ( Paquelet et al, 2022 ; Figure 2 ). A battery of canonical signaling pathways is involved in the 5-HT-mediated system, including the phosphatidylinositol 3-kinase/protein kinase B/ mammalian target of rapamycin (PI3K-Akt/mTOR) signaling pathway, extracellular signal-regulated kinase/mitogen-activated protein kinase (ERK/MAPK) signaling pathway ( Albert and Vahid-Ansari, 2019 ), and cAMP response element-binding protein/cAMP response element-binding protein (PKA/CREB) pathway ( Yue et al, 2022 ; Lin et al, 2023 ).…”
Section: Influence Of Different Neuronal and Glial Systems On Movemen...mentioning
confidence: 99%